Exploring unmet needs and preferences of young adult stroke patients for post-stroke care through PROMs and gender differences - Ibrahim, Sarah; Francis, Troy; Sheehan, Kathleen A.; Kokorelias, Kristina; Stanimirovic, Aleksandra; Hashmi, Syeda; Kalocsai, Csilla; Ng, Sharon; Berkhout, Suze G.; Cameron, Jill I.; Rac, Valeria; Pikula, Aleksandra (Frontiers in Stroke, 2024)
Background: Stroke incidence among young adults of working age (under 65 years of age) has significantly increased in the past decade, with major individual, social, and economic implications. There is a paucity of research exploring the needs of this patient population. This study assessed: 1) young adult stroke patients’ physical, psychological, and occupational functioning and health-related quality of life (HRQoL); and 2) post-stroke care preferences using patient-reported outcome measures (PROMs), with attention to gender differences. Methods: A cross-sectional pilot study was conducted. Sociodemographic and clinical characteristics were collected through chart review and data on occupational function, physical, psychological, and social well-being >90 days post-stroke through a self-reported survey. Descriptive statistics, gender-based, and regression analyses were conducted. Results: The sample included 85 participants. Participants reported impairments in both, occupational functioning, with 58.7% not returned to work (RTW), and HRQoL, specifically with social activities (37%), anxiety (34%), and cognitive function (34%). Women had significantly (p<0.05) worse physical symptoms (sleep disturbance and fatigue), emotional health (depression, stigma, emotional dyscontrol) scores, and sense of self-identify post-stroke. Over 70% of participants preferred in-person post-stroke care led by health care providers and felt they would have benefited from receiving information on physical health (71.4%), emotional and psychological health (56.0%), RTW (38.1%), and self-identity (26.2%) post-stroke. Women preferred cognitive behavioral therapy (p= 0.018) and mindfulness-based stress reduction therapy (p=0.016), while men preferred pharmacotherapy (p=0.02) for psychological symptoms. Conclusion: This is the first study to report impaired HRQoL, psychological and occupational functioning using PROMs, with significant gender differences and preferences for post-stroke care delivery among young adult stroke patients at >90days after stroke. The findings highlight the importance of needs, gender, and age-specific post-stroke education and interventions.